2008
DOI: 10.4136/ambi-agua.50
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of antimicrobial-resistant Enterobacteriaceae in water from different sources in a subtropical region of Argentina

Abstract: In order to determine the occurrence of antimicrobial-resistant Enterobacteriaceae, 506 samples of drinking water, surface water, and ground water were studied in the province of Chaco, Argentina. One hundred and ninety one isolates of Enterobacteriaceae Family members were obtained. The most frequent specie was Escherichia coli and it showed the highest rate of acquired resistance, being the β-lactams the most affected antibiotics. The findings of the present work suggest that the occurrence of antimicrobial-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…Shrestha (2008) also found high resistance among drinking water isolates against Ampicillin (93.9%). Losch et al (2008) in Argentina and Tambedkar et al (2008) in India found that Ampicillin was least effective antibiotic for water isolates. Our study indicated higher percentage of AR and MAR bacteria in drinking water samples.…”
Section: The Mean Free Residual Chlorine (Frc) Mean Combinedmentioning
confidence: 97%
“…Shrestha (2008) also found high resistance among drinking water isolates against Ampicillin (93.9%). Losch et al (2008) in Argentina and Tambedkar et al (2008) in India found that Ampicillin was least effective antibiotic for water isolates. Our study indicated higher percentage of AR and MAR bacteria in drinking water samples.…”
Section: The Mean Free Residual Chlorine (Frc) Mean Combinedmentioning
confidence: 97%
“…The isolates also displayed resistance to multiple antibiotics (4 to 7). Bacteria from these genera have been reported to possess multidrug resistance 38,39 . Six (6) multi-drug resistant bacteria isolated from household water samples were analyzed for plasmid out of which 4 harbored more than one plasmid.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were collected in sterile 250-ml polypropylene bottles, according to internationally recommended methodology [10]. Samples were kept at 4°C until their arrival to laboratory.…”
Section: Methodsmentioning
confidence: 99%